Party Discourse and Prejudiced Attitudes toward Migrants in Western Europe at the Beginning of the 2000s. Issue 3 (September 2016) - Careja, Romana
Building on framing research and on cognitive dissonance theory, the paper examines the differentiated moderating effect of party discourse on prejudiced attitudes against immigrants. Using ESS 2002 data, the study finds that individuals who are positively oriented toward immigrants become more so when confronted with party discourses with anti-immigrant tones. This effect is, however, visible only when it comes to acceptance in one's private sphere, that is, acceptance of inter-ethnic marriage. The study also found some evidence that friendship with immigrants is not strong enough to impede natives to accept the idea of deporting unemployed immigrants.